2022
DOI: 10.1172/jci.insight.161577
|View full text |Cite
|
Sign up to set email alerts
|

Hypo-osmolar rectal douche tenofovir formulation prevents simian/human immunodeficiency virus acquisition in macaques

Abstract: In spite of the rollout of oral pre-exposure prophylaxis (PrEP), the rate of new HIV infections remains a major health crisis. In the United States, new infections occur predominantly in men having sex with men (MSM) in rural settings where access to PrEP can be limited. As an alternative congruent with MSM sexual behavior, we have optimized and tested tenofovir (TFV) and analog-based iso-osmolar and hypo-osmolar (HOsm) rectal douches for efficacy against rectal simian/human immunodeficiency virus (SHIV) infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…A phase I dose escalation study of a tenofovir douche demonstrated excellent acceptability, no toxicity, full explant suppression, and colorectal tissue cell concentrations of tenofovir diphosphate from 1 h through 72 h after a single dose that exceeded concentrations achieved with the on-demand douche or oral TDF/FTC (48,49). Macaque studies indicate superior SHIV (simian/human immunodeficiency virus) protection with a single weekly tenofovir douche when compared to daily oral TDF/FTC dosing (50). The PREVENT Program has recently begun phase I studies of a douche formulation of griffithsin, a red algae-derived lectin that is a highly potent viral entry inhibitor with broad activity against HIV, HSV-2, HCV (hepatitis C virus), and other enveloped viruses.…”
Section: Medicated Anal Lubricants and Douchesmentioning
confidence: 99%
“…A phase I dose escalation study of a tenofovir douche demonstrated excellent acceptability, no toxicity, full explant suppression, and colorectal tissue cell concentrations of tenofovir diphosphate from 1 h through 72 h after a single dose that exceeded concentrations achieved with the on-demand douche or oral TDF/FTC (48,49). Macaque studies indicate superior SHIV (simian/human immunodeficiency virus) protection with a single weekly tenofovir douche when compared to daily oral TDF/FTC dosing (50). The PREVENT Program has recently begun phase I studies of a douche formulation of griffithsin, a red algae-derived lectin that is a highly potent viral entry inhibitor with broad activity against HIV, HSV-2, HCV (hepatitis C virus), and other enveloped viruses.…”
Section: Medicated Anal Lubricants and Douchesmentioning
confidence: 99%